2019
DOI: 10.1017/s2040174419000412
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy obesity is associated with lower psychomotor development scores in boys at age 3 in a low-income, minority birth cohort

Abstract: Whether maternal obesity and gestational weight gain (GWG) are associated with early-childhood development in low-income, urban, minority populations, and whether effects differ by child sex remain unknown. This study examined the impact of prepregnancy BMI and GWG on early childhood neurodevelopment in the Columbia Center for Children’s Environmental Health Mothers and Newborns study. Maternal prepregnancy weight was obtained by self-report, and GWG was assessed from participant medical charts. At child age 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…However, it is important to note that all infants in this cohort were preterm [29]. In contrast, other research has suggested that children born to mothers with high BMI may exhibit slower motor development in male individuals, but not female individuals [30]. It is worth noting that these studies differ in various aspects, including the treatment of maternal BMI (continuous or separated/combined for overweight/obesity), the specific neuropsychological development measures employed, the age at which assessments were conducted, as well as the confounding factors included in each model, making it challenging to compare outcomes directly.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that all infants in this cohort were preterm [29]. In contrast, other research has suggested that children born to mothers with high BMI may exhibit slower motor development in male individuals, but not female individuals [30]. It is worth noting that these studies differ in various aspects, including the treatment of maternal BMI (continuous or separated/combined for overweight/obesity), the specific neuropsychological development measures employed, the age at which assessments were conducted, as well as the confounding factors included in each model, making it challenging to compare outcomes directly.…”
Section: Discussionmentioning
confidence: 99%
“…Our observed associations between elevated maternal pre-pregnancy BMI and classification of having obesity with poorer child cognitive performance at age three, specifically for FSIQ, verbal, and information score subsets of the WPPSI, is consistent with previous literature findings where higher maternal BMI is associated with poorer child cognitive outcomes. 5,45 Pregnancy is associated with changes in the maternal inflammatory milieu, and obesity also contributes to chronic, sub-clinical inflammation, which has been linked to adverse health outcomes for the infant and mother. 46 This pro-inflammatory intrauterine environment may have impacts on congenital structural defects and overall childhood cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Birth parent weight retention was calculated by subtracting self-reported prepregnancy weight from the weight measured at the child age 7-y visit. Birth parent obesity was defined as a BMI ≥ 30 kg/m 2 per Center for Disease Control guidelines and previously used in this population [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…For cardiometabolic clusters, sensitivity analyses were created excluding those children who had metabolic visits before age 9 y. Finally, all models were fit with inverse probability sample weighting to account for whether associations were affected by attrition or incomplete follow-up at child age 7 y, as previously described in this cohort [ 29 , 31 , 36 , 37 ]. Inverse probability weighting estimates and corrects for bias due to missing data by applying more weight to participants included in the final sample who have similar characteristics to participants not included in the sample due to incomplete or missing data.…”
Section: Methodsmentioning
confidence: 99%